On equivalence of Duffin-Kemmer-Petiau and Klein-Gordon equations - Fainberg, V. Ya. [UNESP]; Pimentel, B. M. [UNESP] (Sociedade Brasileira de Física, 2000)
A strict proof of equivalence between Duffin-Kemmer-Petiau (DKP) and Klein-Gordon (KG) theories is presented for physical S-matrix elements in the case of charged scalar particles interacting in minimal way with an external or quantized electromagnetic field. First, Hamiltonian canonical approach to DKP theory is developed in matrix form. The theory is then quantized through the construction of the generating functional for Green functions (GF) and the physical matrix elements of S-matrix are proved to be relativistic invariants. The equivalence between both theories is then proved using the connection between GF and the elements of S-matrix in reduction formulas of Lehmann, Symanzik, Zimmermann.